Morphology and genetics characteristics of Steinernema guangdongense Qiu, Fang & Zhou, 2004 from Vietnam - Duyen, Nguyen Thi; Son, Nguyen Giang; Chau, Nguyen Ngoc (Academia Journal of Biology, 2013)
During survey on entomopathogenic nematodes carried out in 2004, a new record of the genus Steinernema (S-XT) was isolated from a soil sample that collected from Xuan Trach, Quang Binh province. The morphological and molecular identification of S-XT isolate have revealed scientific name as Steinernema guangdongense Qiu, Fang & Zhou, 2004. Generally, the specimens from Vietnam are similar to the original description of S. guangdongense by having eight lines in the lateral fields at infective juveniles; the presence of a small double flapped epiptygma, a small projection on the dorsal side of the tail tips and its prominent post-anal swelling part, which is typical for S. guangdongense. In males, the spicules paired, brown color, head (manubrium) of spicules with rounded anterior end, almost continuous with shaft, except body length of females at the first generation always larger. The morphology, morphometrics and molecular characterization based on Vietnamese specimens were supplemented data for the redescription of S. guangdongense and confirmed it belonging to “glaseri” group with the body length of infective juveniles fluctuated between 1,055 µm and 1,063 µm and eight lines in lateral fields. The newly recorded species is also close to S. longicaudum, which was also recorded from Vietnam but differed from it by having another morphological structure of the spicules apparatus, present of the paired epiptigma in the female and the numbers of the lateral fields in the infective juveniles.